An Econometric Study on Office Rental Market in Kuala Lumpur - Badrul Hisyam, Ab. Lah (2011)
The intense competition among property investors has been fueled by the limited pool of desired assets. As global markets become more developed and matured, the yield is becoming more compressed, which resulted in property investors to expand their property investment portfolio across the geography borders. As a result, commercial real estate investment has been globalised to a new unprecedented level, due to the diversification strategies by these global property investors. Kuala Lumpur, being the financial and economic capital of Kuala Lumpur is not spared from being in the radar of global property investors. In addition to Kuala Lumpur, other major urban centres in Malaysia are Penang and Johor Bahru. While the office space market in Kuala Lumpur has an international appeal, the same notion is yet to be confirmed for both Penang and Johor Bahru office space market. The main objective of this study is to explore the economic indicators such as GDP, CPI, unemployment rate and the interest rate to the demand and supply factors that determine the rental value of office space market. The demand factor is represented by the natural vacancy rate of the office space, while the supply factor is represented by the total office floor space. Next, the study compare whether the changes in economic indicators will change the variation in the office rental market in Kuala Lumpur, Penang and Johor Bahru. This study covers the office rental values in various business districts in Kuala Lumpur, other urban centres in Klang Valley area and also other major urban centres in the country, namely Penang and Johor Bahru. The regression analysis on office rental market in Klang Valley, Johor Bahru and Penang suggests that both geographical clusters have different rental rate determinants of office space. The model implies that the office rental market in Kuala Lumpur is very much dictated by supply and demand factors. As for the office rental market in Johor Bahru and Penang, the model suggests a direct relationship between office space supply and service sector productivity level. Office rental market in Johor Bahru and Penang is very sensitive to the changes of office space supply. In contrast, an increase of service sector output, as evident in GDP service factor, will help to spur demand to occupy office space in Johor Bahru and Penang, thus help to contribute positively on the office space rental rates.